High‐Fat and High‐Sucrose Diets Impair Time‐of‐Day Differences in Spatial Working Memory of Male Mice. Issue 12 (11th October 2020) - Davis, Jennifer A.; Paul, Jodi R.; McMeekin, Laura J.; Nason, Shelly R.; Antipenko, Jessica P.; Yates, Stefani D.; Cowell, Rita M.; Habegger, Kirk M.; Gamble, Karen L.
Abstract : Objective: This study aimed to investigate both the long‐term and short‐term impacts of high‐fat diets (HFD) or high‐sucrose diets (HSD) on the normal diurnal pattern of cognitive function, protein expression, and the molecular clock in mice. Methods: This study used both 6‐month and 4‐week feeding strategies by providing male C57BL/6J mice access to either a standard chow, HFD, or HSD. Spatial working memory and synaptic plasticity were assessed both day and night, and hippocampal tissue was measured for changes in NMDA and AMPA receptor subunits (GluN2B, GluA1), as well as molecular clock gene expression. Results: HFD and HSD both disrupted normal day/night fluctuations in spatial working memory and synaptic plasticity. Mice fed HFD altered their food intake to consume more calories during the day. Both diets disrupted normal hippocampal clock gene expression, and HFD reduced GluN2B levels in hippocampal tissue. Conclusions: Taken together, these results suggest that both HFD and HSD induce a loss of day/night performance in spatial working memory and synaptic plasticity as well as trigger a cascade of changes that include disruption to the hippocampal molecular clock.